ORGANIC WASTE RECYCLING AS A BUSINESS MODEL FOR LIVESTOCK AND CROP PRODUCTION IN UZBEKISTAN: BARRIERS, DRIVERS AND IMPLEMENTATION WAYS (British Journal of Global Ecology and Sustainable Development, 2026)
Uzbekistan’s municipal solid waste (MSW) generation has reached approximately 14 million tons annually, with organic residues-primarily food and vegetable waste-comprising 25% of the total volume. Despite this substantial biomass potential, large-scale valorization is currently hindered by fragmented business frameworks and limited investment incentives. This study employs a circular economy lens to evaluate the technical and economic viability of three strategic pathways: composting/vermicomposting, anaerobic digestion (AD), and Black Soldier Fly (BSF) larvae bioconversion.